A Study of Corruption in India - Singh, Chitranjan (Management Journal for Advanced Research, 2022)
For a nation, economic growth is crucial since the amount of economic growth impacts people's standard of living and is regarded as a good proxy for human progress. Corruption is one of the ideologies recognized to have an impact on a nation's economic prosperity. Scholarly research on the subject of the various effects of corruption on economic performance is examined in this study. As a case study, we've used India as an example. We used a correlation study to support our claims that corruption has a detrimental impact on economic growth. Data on corruption perception (CPI), GDP, GDP growth rate, and FDI have all been used in our analysis. It is thus an attempt to investigate the empirical link between corruption and economic development.